Current use of catheter directed treatment of acute PE in Europe: results of survey of EAPCI and ESC Working Group on Pulmonary Circulation and Right Ventricular Function. (14th October 2021) - Roik, M; Pruszczyk, P; Klok, F A; Barco, S; Jermakow, M; Dudek, D
Abstract: Aims: This survey conducted by the European Association of Percutaneous Cardiovascular Interventions (EAPCI) and ESC Working Group on Pulmonary Circulation & Right Ventricular Functioncollected information on current practices in catheter-directed treatment (CDT) of acute pulmonary embolism (PE) among cardiology intervention centers in European countries. Methods and results: Responses from 157 Catheterization laboratories (Cath Lab) representing European countries were collated and analyzed.Sixty seven centers (43%) centers reported application of CDT in PE patients. Almost all centers performing CDT (96%) provided 24/7 service and had experience with a wide spectrum of percutaneous interventions including those for the treatment of structural heart diseases; 53% of the Cath labs utilizing CDT were located in teaching hospitals, and involved 5 to 10 interventional cardiologists performing more than 600 coronary procedures per year. The survey showed a rapid increase in CDT use in European countries after 2015 (45 out of 67 centers). Over 60% of responding centers performed 5–10 CDT procedures per year. It was estimated that 24 patients were treated with CDT per center on a yearly base. The majority of centers (80.3%) indicated that CDT is used in high-risk PE patients, while 38% also apply CDT to intermediate high risk PE. The survey revealed that pigtail catheters are most commonly used for CDT (49%), while dedicated systems such as AngioJet, Indigo and EKOS were reported to be used in 25%, 23.81% and 20.24% of the centers, respectively. Local thrombolysis during CDT was used in 71% of the procedures. More than 60% of the responders indicated that according to their expert opinion CDT will be routinely used in PE patients in the future. However, they stressed the need for randomized trials to evaluate the safety and efficacy of CDT and determine the patients that would benefit most. Conclusions: According to the survey, use of CDT in patients with PE is increasing over time. Currently, it is mostly but not exclusively applied to patients with high-risk PE. The respondents indicated the need for high-quality randomized trials to establish the optimal indication for CDT and further standardize the use of the available techniques. FUNDunding Acknowledgement: Type of funding sources: None.